1994
DOI: 10.1172/jci117305
|View full text |Cite
|
Sign up to set email alerts
|

The central role of chromatin in autoimmune responses to histones and DNA in systemic lupus erythematosus.

Abstract: To gain insight into the mechanisms of autoantibody induction, sera from 40 patients with systemic lupus erythematosus (SLE) were tested by ELISAs for antibody binding to denatured individual histones, native histone-histone complexes, histone-DNA subnucleosome complexes, three forms of chromatin, and DNA. Whole chromatin was the most reactive substrate, with 88% of the patients positive. By chi-square analysis, only the presence of anti-(H2A-H2B), anti-[(H2A-H2B) -DNA], and antichromatin were correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
177
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(193 citation statements)
references
References 49 publications
13
177
0
3
Order By: Relevance
“…In both human and animal models of SLE, it is well known that autoantibodies to chromatin components such as DNA and histones commonly accompany the development of glomerulonephritis and flares of the disease. [25][26][27] Indeed, there is evidence that antibodies to histones and dsDNA participate in the pathogenesis of glomerulonephritis (reviewed in Berden 25 ). The presence of antihistone antibodies in these mice in the absence of antibodies to dsDNA is consistent with the observation that histone autoantibodies precede the appearance of anti-dsDNA in MRL/lpr mice 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both human and animal models of SLE, it is well known that autoantibodies to chromatin components such as DNA and histones commonly accompany the development of glomerulonephritis and flares of the disease. [25][26][27] Indeed, there is evidence that antibodies to histones and dsDNA participate in the pathogenesis of glomerulonephritis (reviewed in Berden 25 ). The presence of antihistone antibodies in these mice in the absence of antibodies to dsDNA is consistent with the observation that histone autoantibodies precede the appearance of anti-dsDNA in MRL/lpr mice 27 .…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] Indeed, there is evidence that antibodies to histones and dsDNA participate in the pathogenesis of glomerulonephritis (reviewed in Berden 25 ). The presence of antihistone antibodies in these mice in the absence of antibodies to dsDNA is consistent with the observation that histone autoantibodies precede the appearance of anti-dsDNA in MRL/lpr mice 27 . Thus, it appears that the Pten +/À and Pten +/À SHIP +/À mice develop a pattern of antichromatin antibodies similar to that of a spontaneous model of SLE and glomerulonephritis.…”
Section: Resultsmentioning
confidence: 99%
“…SLE is a disease that is characterized by the production of autoantibodies of multiple specificities, although typically, such antibodies are directed at groups of nucleus-related antigens such as DNA, RNA and nuclear proteins [34][35][36][37][38][39]. Although there is evidence for polyclonality in this response, molecular analysis of autoantibodies suggests an antigen and T cell-driven process, because these antibodies show evidence of somatic mutation in their complementarity-determining regions [15,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…the amino-and carboxyl-terminal domains [21]. Since during the course of some autoimmune diseases like systemic lupus erythematosus (SLE) the elicited anti-histone antibodies are directed mainly against the histone 'tails' exposed on the nucleosomes [34], it has been suggested that chromatin cores rather than free histones would be responsible for the triggering of the humoral response [35]. Taking into account the equivalent locations of the antigenic determinants of the histones which are recognized by both SLE and VL sera, it is likely that a similar mechanism of epitope selection must operate during both pathological processes.…”
Section: Discussionmentioning
confidence: 99%